TheAnalysis of the Workload of Civil Servants in the Marine and Fisheries Service of Boalemo Regency - isra misriani botutihe isra; djamila podungge; samin latif (Journal of Economic, Business, and Administration (JEBA), 2023)
Workload analysis is a method of knowing the workload so that it can be known to employees needed to complete the workload of the task and the time given. The purpose of this study is to find out the workload of civil servants in the Marine and Fisheries Service of Boalemo Regency.This study refers to a quantitative approach that is the action of a researcher to find the results of research using data in the form of numbers.Civil Servants' expense analysis of Boalemo District of Marine and Fisheries Office includes Establishing available working time so that work time is needed, determining workload standards, determining the standard of leniency during the specified time, and calculating HR needs.